Index-Driven Digitization and Indexation of Historical Archives - Colavizza, Giovanni; Ehrmann, Maud; Bortoluzzi, Fabio (Frontiers in Digital Humanities, 2019)
The promise of digitization of historical archives lies in their indexation at the level of contents. Unfortunately, this kind of indexation does not scale with the speed of digitization if done manually. In this article we present a method to bootstrap the deployment of a content-based information system for digitized historical archives, relying on extant indexing tools. Such indexes were commonly prepared to search within homogeneous records when the archive was still current. We present a conceptual model to describe and manipulate historical indexing tools. We then introduce a systematic approach for their use in order to guide digitization campaigns and to index digitized historical records. Eventually, we exemplify the approach with a case study on the indexation system of the X Savi alle Decime in Rialto, a Venetian magistracy in charge for the exaction - and related record keeping - of a tax on real estate in early modern Venice.